Computational predictions on the interactions of parabens with a dipalmitoyl phosphatidylcholine lipid bilayer and the human serum albumin protein - Masone, Diego Fernando (2016)
Parabens are esters of para-hydroxybenzoic acid extensively used as preservatives in cosmetics and pharmaceutics. In the recent years their safe use has been questioned, mainly due to their estrogenic activity, their concentration in breast cancer tissues and their endocrine disrupting consequences on the reproductive system. In this study, the interaction of five forms of paraben ligands (namely methyl, ethyl, propyl, butyl and heptyl) with a model dipalmitoylphosphatidylcholine bilayer and the human serum albumin transport protein, was assessed using extensive atomistic molecular dynamics simulations. Free energy profiles for the insertion of each ligand into the lipid bilayer were computed along an appropriate reaction coordinate. Protein-ligand interactions were evaluated through a combination of an efficient sampling of the protein-ligand hydrogen bond network and the full system side chains, together with an all-atom force field. Simulation results show that among the paraben ligands studied, methyl, propyl and butyl parabens penetrate more easily the bilayer and show higher binding affinity to human serum albumin in terms of their hydrogen bonding network, supporting the experimental hypotheses of their potential risk to human health.